John within Judaism : Religion, Ethnicity, and the Shaping of Jesus-Oriented Jewishness in the Fourth Gospel - Cirafesi, Wally V. (Ancient Judaism and Early Christianity, 2022)
In John within Judaism , Wally V. Cirafesi offers a reading of the Gospel of John as an expression of the fluid and flexible nature of Jewish identity in Greco-Roman antiquity. While many have noted John's general Jewishness, few have given it a seat at the ideologically congested table of ancient Jewish practice and belief. By interrogating the concept of "Judaism" in relation to the complex categories of "religion" and "ethnicity," Cirafesi argues that John negotiates Jewishness using strategies of ethnic identity formation paralleled in other Jewish sources from the Second Temple and early rabbinic periods. In this process of negotiation, including its use of "high christology" and critique of Ioudaioi, John coalesces with other expressions of ancient Jewish identity and, thus, can be read "within Judaism.".